Retraction notice to “The chemistry of group-VIb metal carbonyls” [Eur. J. Chem. 2012, 3(3), 367-394, doi: 10.5155/eurjchem.3.3.367-394.604] - Kaushik, Manish; Singh, Ayodhya; Kumar, Munesh (European Journal of Chemistry, 2021)
Retraction notice to “The chemistry of group-VIb metal carbonyls” [Eur. J. Chem. 2012, 3(3), 367-394, doi: 10.5155/eurjchem.3.3.367-394.604]